217k views
1 vote
Which expressions are equivalent to -90 - 60w? Choose three. *Hint: On each answer choice below, use the distributive property to decide which ones match -90-60w. Also remember that -60w-90 is equivalent to -90-60w a) -30(3 + 2w) b) (-9 − 6w) x 10 c) -3(30 - 20w) d) (6 + 4w) × 15 e) −20(4.5 + 3w)

User Xenyal
by
5.4k points

1 Answer

4 votes

Answer:

a), b), e)

Explanation:

a) -30(3 + 2w) = -90 - 60w

b) (-9 − 6w) x 10 = -90 - 60w

c) -3(30 - 20w) = -90 + 60w

d) (6 + 4w) × 15 = 90 + 60w

e) −20(4.5 + 3w) = -90 - 60w

User Jean Azzopardi
by
5.5k points